(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: diabetes is one of the leading causes of death, and has a huge economic impact on the burden of society. Lifestyle interventions such as diet, physical activity and weight reducing are proven to be effective in the prevention of diabetes. To encourage policy actions, data on the costeffectiveness of such strategies of prevention programmes are needed. Methods: a systematic review of the literature on the cost-effectiveness of prevention strategies focusing on lifestyle interventions for diabetes type 2 patients. A weighted version of Drummond checklist was used to further assess the quality of the included studies. Results: six studies met the inclusion criteria and were therefore considered in this paper. Intensive lifestyle intervention to prevent diabetes type 2 is cost-effective in comparison to other interventions. All studies were judged of medium-to-high quality. Conclusions: policy makers should consider the adoption of a prevention strategy focusing on intensive lifestyle changes because they are proven to be either cost-saving or cost-effective.